A Randomized Trial of a Brief Behavioral Intervention for PrEP Uptake Among Men Who Have Sex With Men at Increased Risk for HIV Infection. (1st July 2021) - Chan, Philip A.; Nunn, Amy; van den Berg, Jacob J.; Cormier, Kevin; Sowemimo-Coker, Genoviva; Napoleon, Siena C.; Arnold, Trisha; Moitra, Ethan
Abstract : Background: The aim of this study was to evaluate the efficacy of a novel, brief 2-session behavioral intervention to promote HIV pre-exposure prophylaxis (PrEP) uptake among men who have sex with men (MSM) who are behaviorally at risk for HIV. Setting: A pilot randomized controlled trial was conducted at a sexually transmitted infection (STI) clinic to compare a brief motivational interviewing intervention with passive referral only for PrEP uptake. Methods: MSM who scored as "high risk" on the HIV Incidence Risk index for MSM was offered a brief (15–20 minutes) motivational interviewing–based intervention at the time of STI testing to address barriers to PrEP uptake, including low risk perception, stigma, side effects, and cost. The initial session was followed by a brief, telephone booster session that lasted <10 minutes. The primary outcome was attending a clinical PrEP appointment and accepting a prescription for PrEP. Results: Participants were recruited from an urban STI clinic in the United States. A total of 86 MSM who were behaviorally at risk for HIV were enrolled in the study (N = 43 intervention; N = 43 treatment-as-usual, "TAU"). Participants randomized to the intervention were significantly more likely to attend a clinical appointment and accept a prescription for PrEP, compared with treatment-as-usual (52.3% versus 27.9%, respectively; odds ratio = 3.6; 95% confidence interval: 1.5 to 8.9; P = 0.005). Conclusions: A brief behavioral intervention focused on the initial steps in the PrEP care cascade demonstrated preliminary efficacy in promoting uptake among MSM who are behaviorally at risk for HIV.